2016
DOI: 10.2147/ott.s111176
|View full text |Cite
|
Sign up to set email alerts
|

History and progression of Fat cadherins in health and disease

Abstract: Intercellular adhesions are vital hubs for signaling pathways during multicellular development and animal morphogenesis. In eukaryotes, under aberrant intracellular conditions, cadherins are abnormally regulated, which can result in cellular pathologies such as carcinoma, kidney disease, and autoimmune diseases. As a member of the Ca2+-dependent adhesion super-family, Fat proteins were first described in the 1920s as an inheritable lethal mutant phenotype in Drosophila, consisting of four member proteins, FAT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 49 publications
(80 reference statements)
0
40
0
Order By: Relevance
“…On the other hand, FAT atypical cadherin 4 (Fat4), a tumor suppressor gene acting on the Wnt/β-catenin signalling (Cai et al 2015) , is found relatively up-regulated at day7 in neotenic samples compared to metamorphic ones. Another essential function of Fat4 is maintenance of planar cell polarity (PCP) (Zhang et al 2016) , which blastema cells require for exhibiting their positional information. In a recent study (Albors et al 2015) it has been demonstrated that re-expression of PCP genes is crucial for axolotl spinal cord regeneration by orienting mitotic spindles along to anterior-posterior axis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, FAT atypical cadherin 4 (Fat4), a tumor suppressor gene acting on the Wnt/β-catenin signalling (Cai et al 2015) , is found relatively up-regulated at day7 in neotenic samples compared to metamorphic ones. Another essential function of Fat4 is maintenance of planar cell polarity (PCP) (Zhang et al 2016) , which blastema cells require for exhibiting their positional information. In a recent study (Albors et al 2015) it has been demonstrated that re-expression of PCP genes is crucial for axolotl spinal cord regeneration by orienting mitotic spindles along to anterior-posterior axis.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that the atypical cadherin subfamily likely developed a prominent function to shape tissues in two ways dependent on tissue character: i) in migratory tissue via retrograde Myo-II movement and ECM-dependent mechanism (Fat2-Myo-II in Drosophila egg chambers in this work) and ii) in moving but non-ECM-migratory tissue via intercalations (Dachsous-MyoID in the Drosophila hindgut 37 , Fat-Dachsous-Dachs in the Drosophila wing 38 ). As Fat2 close homologs, namely Fat1-3, exist in vertebrates 39 , it is likely that similar conserved mechanisms are used to move and sculpt tissues and organs in vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer, it is an established biomarker for triple negative, advanced cancers with poor prognosis (Doberstein et al, 2014;Altevogt et al, 2016) specifically due to changes in sialylation linked to metastasis (Hoja-Łukowicz et al, 2013). A second cell adhesion protein we identified was FAT atypical cadherin 1 (FAT1), a highly glycosylated cadherin-like protein that plays a role in cell migration, lamellipodia dynamics, cell polarity, and cell-cell adhesion (Katoh, 2012;Zhang et al, 2016). FAT1 repression in cancer occurs due to homozygous deletion or epigenetic silencing and is preferentially downregulated in invasive breast cancer (Katoh, 2012).…”
Section: Flux-based Regulation Of Sialoglycosites-global Considerationsmentioning
confidence: 99%